Incidence and effect of secondary cardiac amyloidosis on outcomes of patients with t(11;14) multiple myeloma - Wang, Jinghua; Yang, Shuo; Liao, Pengjun; Zeng, Lingji; Ling, Wei; Wan, Li; Weng, Jianyu; Zhong, Liye (Frontiers in Cardiovascular Medicine, 2022)
Background The t(11;14)(q13;32) is a common chromosome translocation in multiple myeloma (MM), but its prognostic value remains controversial. Immunoglobulin light chain amyloidosis is commonly secondary to multiple myeloma, which can rapidly cause heart failure and high mortality. We aimed to investigate the prevalence of secondary cardiac amyloidosis in MM patients with t(11;14) and to evaluate its impact on survival outcomes. Methods We retrospectively identified 52 MM patients with t(11;14) in our center between October 2015 and April 2022. The associations between cardiac amyloidosis and clinical and biological parameters were statistically analyzed, and the impacts of concomitant of cardiac amyloidosis on survival and prognosis of MM patients with t(11;14) were also assessed. Results Concomitant presence of cardiac amyloidosis was observed in 15 (28.8%) of all cases. Patients with cardiac amyloidosis had significantly higher NT-proBNP (p = 0.002) and higher hs-cTnT (p < 0.001), while the patients without cardiac amyloidosis had higher percentage of bone marrow plasma cells (p = 0.027), higher incidence of hemoglobin <80 g/L (p = 0.021) and bone destruction (p < 0.001). The median overall survival (OS) for all patients was 33.4 months after a median follow-up of 23.8 months. The amyloidosis group showed a significantly shorter OS than the non-amyloidosis group (15.3 vs. 41.8 months, p < 0.001). Besides, patients harboring NT-proBNP >1,800 pg/ml (p < 0.001) or hs-cTnT ≧40 pg/ml (p = 0.001) or light chain (LC) only isotype (p = 0.033) had a significantly shorter mean OS compared with patients with lower NT-proBNP or hs-cTnT or other M-protein isotype. Univariate analyses showed that NT-proBNP >1,800 pg/ml, hs-cTnT ≧40 pg/ml, LC only isotype, and concomitant presence of cardiac amyloidosis were independently associated with shorter OS, while NT-proBNP >1,800 pg/ml still retained the prognostic value for OS in multivariate analyses. Conclusion The t(11;14) MM patients with coexisting cardiac amyloidosis may represent a distinct clinical entity that confers a poor outcome. These findings may have important clinical and biological implications.